Neuromuscular adaptations to single-session combined strength and endurance training in untrained men : an examination of the order effect - Pulverenti, Timothy (2013)
Understanding the adaptations to single-session combined strength (S) and endurance (E) training has received increased attention in scientific literature through the expand-ing use of combined training programs for practical purposes. However, the intra-session exercise order when performing both E and S in the same training session may limit potential strength development, as the neuromuscular adaptations to either training mode alone are very different. Research on the effect of the intra-session exercise order of combined training on various training-induced adaptations, i.e. the order effect, is currently limited, especially with regard to the neuromuscular adaptations. Therefore, the purpose of this study was to investigate the order effect to single-session combined strength and endurance training on the long-term neuromuscular adaptations.